2018
DOI: 10.3201/eid2410.180730
|View full text |Cite
|
Sign up to set email alerts
|

Non-cyp51AAzole-ResistantAspergillus fumigatusIsolates with Mutation in HMG-CoA Reductase

Abstract: The recent increase in azole-resistant Aspergillus fumigatus is a global concern. Identifying the mutations that confer azole resistance is essential for developing novel methods for prompt diagnosis and effective drug treatment. We screened A. fumigatus clinical isolates for novel mutations conferring azole resistance. We compared the genomic sequences of susceptible and resistant isolates without mutations in cyp51A (non-cyp51A) and found mutations in hmg1 and erg6 involved in ergosterol biosynthesis. We als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
92
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(94 citation statements)
references
References 32 publications
1
92
0
1
Order By: Relevance
“…We confirmed the presence of azole resistance by using the Clinical Laboratory Standard Institute method (Appendix Table 1) (2). Isolates resistant to >1 medical azoles (itraconazole, voriconazole, posaconazole, and isavuconazole) were defined as azole-resistant A. fumigatus and examined for resistance mechanisms, microsatellite-based phylogenetic relatedness, and growth rates following previously described methods (3,4).…”
Section: Multicenter Study Of Azole-resistant Aspergillus Fumigatus Cmentioning
confidence: 99%
See 1 more Smart Citation
“…We confirmed the presence of azole resistance by using the Clinical Laboratory Standard Institute method (Appendix Table 1) (2). Isolates resistant to >1 medical azoles (itraconazole, voriconazole, posaconazole, and isavuconazole) were defined as azole-resistant A. fumigatus and examined for resistance mechanisms, microsatellite-based phylogenetic relatedness, and growth rates following previously described methods (3,4).…”
Section: Multicenter Study Of Azole-resistant Aspergillus Fumigatus Cmentioning
confidence: 99%
“…Overexpression of cdr1B (a drug efflux transporter) and an S269P mutation in hmg1 (a hydroxymethylglutaryl-CoA reductase) were identified in 4 resistant isolates but not in the initial susceptible isolate (Appendix Table 5, Figure 4), suggesting their roles involved in azole resistance (4,9). Another 2 pan-azole-resistant respiratory isolates were recovered from a patient (no.…”
Section: Multicenter Study Of Azole-resistant Aspergillus Fumigatus Cmentioning
confidence: 99%
“…The current A. fumigatus PCR-based resistance assays do not reveal the less common or potential mutations involved in azole resistance. In Manchester, 43% of the azole-resistant patient isolates were reported to be non-cyp51A related [26] and numerous studies have revealed that azole resistance is most certainly due to other genes [46][47][48][49][50][51][131][132][133][134]. Besides gene mutations in the ergosterol biosynthesis pathway, other non-cyp51A-mediated resistance mechanisms involve the overexpression of drug efflux transporters such as ABC-and MFS-transporters [96,[135][136][137].…”
Section: The Pyrosequencing Methodsmentioning
confidence: 99%
“…Mutations in genes involved in the A. fumigatus ergosterol biosynthetic pathway, including hmg1, erg6, cyp51A and cyp51B among others, are described as having a role in azole resistance [26,[46][47][48][49][50][51]. The means for testing non-cyp51A-mediated mechanisms of resistance lag far behind and therefore, for the purpose of this discussion, we concentrate on cyp51A.…”
Section: Azole Resistancementioning
confidence: 99%
“…Most of the isolates harbored the mutation at G54, which is a hotspot site in A. fumigatus Cyp51A with variable substitutions (G54E, G54W, and G54R) ( Table 2). The VRCZ-resistant strains were isolated from patients with a history of VRCZ treatment; all of these isolates had the G448S mutation 19,20) . The first azole-resistant strain with a tandemrepeat mutation (TR46/Y121F/T289F) in Japan was clinically isolated in 2013 9) , followed by isolation of the TR34/L98H strain (OKH50) in 2016 21) .…”
Section: Azole-resistant a Fumigatus Isolates In Japanmentioning
confidence: 99%